2014
DOI: 10.4161/15384101.2014.950126
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CDK-mediated phosphorylation of Smad3 results in decreased oncogenesis in triple negative breast cancer cells

Abstract: Keywords: CDK, cyclin, paclitaxel, Smad3, triple negative breast cancer Abbreviations: BCSC, breast cancer stem cells; CDK, cyclin dependent kinase; CDKi, cyclin dependent kinase inhibitor; CK, cytokeratin; EGFR, epidermal growth factor receptor; EMT, epithelial-mesenchymal transition; ER, estrogen receptor; HER2, human epidermal growth factor receptor 2; Pin1, peptidyL-prolyl cis-trans isomerase NIMA-interacting 1; PR, progesterone receptor; TNBC, triple negative breast cancerBreast cancer onset and disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…Multiples studies have revealed that, in breast cancer patients, the expression of connexin proteins is correlated with clinicopathological biomarkers, including estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), which are normally used to predict the response of mammary cancer patients to therapy (33,53). The Hs578T cell line used in the current study is a type of triple-negative breast cancer (TNBC), while the MCF-7 cell line is non-TNBC (ER+ and PR+) (54,55). ER and PR status have traditionally been used to select patients suitable for tamoxifen treatment (56).…”
Section: A B Discussionmentioning
confidence: 99%
“…Multiples studies have revealed that, in breast cancer patients, the expression of connexin proteins is correlated with clinicopathological biomarkers, including estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2), which are normally used to predict the response of mammary cancer patients to therapy (33,53). The Hs578T cell line used in the current study is a type of triple-negative breast cancer (TNBC), while the MCF-7 cell line is non-TNBC (ER+ and PR+) (54,55). ER and PR status have traditionally been used to select patients suitable for tamoxifen treatment (56).…”
Section: A B Discussionmentioning
confidence: 99%
“…In addition, we observed a higher expression of pCHK2-Thr68 in TNBC tissues than non-TNBC tissues. Greater activation of the cell cycle checkpoint protein (e.g., CDK) may be associated with the increased activity of TNBC stem cells [25,26] as accumulated p53 tumor suppressor gene and BRCA1 gene mutations may trigger ATM/ATR–CHK1/2–CDC25C pathways [27,28]. Such increases in pCHK2-Thr68 also occur in other tumors such as mucinous adenocarcinomas and colorectal cancer [29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of cyclins, and the consequent impact on CDK activity, induces inhibitory noncanonical phosphorylation of Smad3. Collectively, these events result in the blockade of canonical, Smad3-mediated tumor suppression, thereby contributing to breast cancer progression and metastasis [19,21,22]. In pre-clinical studies, pharmacologic CDK inhibition has restored the canonical tumor suppressant actions of Smad3 signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Additional predictive markers and novel therapeutics directed toward cyclins/CDKs and TGFb signaling are also in active development [19]. Smad3 is a transcriptional regulator that canonically functions through phosphorylation at the C-terminus to facilitate tumor suppression [20].…”
Section: Introductionmentioning
confidence: 99%